CHARACTERIZATION OF ROOT-ASSOCIATED RHIZOBACTERIA INCLUDING BACILLUS MESONAE FOR BIOINOCULANT POTENTIAL IN VIGNA UNGUICULATA - Radha Yadamuri, Reddivari Lavanya, Kodatham Reddy Sai Harshavardhan, Yarava Yaswanth Kumar, Inani Pavan Sai (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2025)
Leguminous crops such as Vigna unguiculata (cowpea) harbor symbiotic and as- sociative root bacteria that play a vital role in soil fertility and plant growth. This study focuses on isolating and characterizing root-associated bacteria particularly Rhizobium spp. and Bacillus mesonae with potential for eco-friendly biofertilizer development. Root nodules and rhizospheric soil were collected from cowpea plants in Chinnagottigallu village, Andhra Pradesh, and bacterial isolates were obtained using selective media. Morphological, biochemical, and molecular identification using 16S rRNA gene sequencing was carried out for accurate classification. Func- tional assays assessed indole-3-acetic acid (IAA) production and nitrogen fixation potential. The Bacillus mesonae and Rhizobium isolates demonstrated traits that support plant growth, improve nutrient uptake, and enhance soil health. These native microbial isolates hold promise as sustainable alternatives to synthetic fertilizers, promoting soil health and crop productivity. Field trials are recommended to evaluate their efficacy across diverse agroecological zones.